Fungos micorrízicos arbusculares e aspectos nutricionais de três espécies perenes de um SAF em Manaus-AM - Oliveira, Lucas Henrique (2019)
The arbuscular mycorrhizal fungi (FMAs) are symbionts of soil have been studied for exercising a significant role in the functionality and maintenance of natural ecosystems managed and mostly degraded. The colonization of AMF allows better utilization of nutrients and water available in the soil by the host plants, contributing to the nutrition as they facilitate this absorption. The present study aimed to evaluate the occurrence of AMFs in the Andirobeira, Sapoteira do Solimões and Cupuaçuzeiro rhizosphere present in an Agroforestry System, being evaluated in four months (march, june, september and december) of 2018. The 3x4 factorial scheme was analyzed and the the treatment means were compared by Tukey test. Person's linear correlation coefficient was used to correlate mycorrhizal colonization with the chemical characteristics of rhizospheres and the macro and micronutrient contents in plant leaf tissues. The spore density of AMF in the rhizospheres showed significant variation (p <0,05) between the months of collection and perennial species. It was verified that the rhizospheres of Sapoteira do Solimões and Andirobeira presented the highest spore density averages (76,2 and 70,4 spores.50 g of soil-1 ). In march, a sample with 97 spores.50 g of soil-1 was found. The highest rates of mycorrhizal colonization (%) were observed in the Sapoteira do Solimões and Andirobeira rhizospheres, which differed statistically from Cupuaçuzeiro, with no statistical difference between the months of collection. The genus Glomus spp. was dominant in plant rhizospheres (43,1%), being the least abundant Gigaspora spp. (10,04%). The global correlations were positive for the Ca, Mg, Fe, Zn, Mn, MO and pH (H2O) variables of the rhizospheric soil. n view of the above, it can be concluded that despite the low r values found in the correlations, there were positive correlations between the symbiotic association of AMFs and the nutrient content of perennial SAF species. The Cupuaçuzeiro species had more positive correlations between nutrients and mycorrhizal colonization among the species. Showing the importance of symbiotic association for the survival of the species.